Hungarian Monitoring, 9 October 1988 . [Magyar rádiófigyelő], 1988. október 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Algerian situation becomes more critical - Demonstrations in Sweden against Romanian village destructions - Pravda marks centenary of Bukharin's birth - Popular front now also formed in Latvia Domestic Affairs: - New York Times publishes interview with János Kádár entitled "A Hungarian looks back" - "4.5 million fetuses have been butchered in Hungary since 1956": Gábor Czakó expresses his views on the demographic situation and the refusal to have children - Will the Democratic Forum become a party? Founding member Zoltán Bíró's answer to the question - All Swedish parties protest the Romanian village destruction policy - Statement of Hungarian churches' ecumenical council letter defending national minorities in Romania - Csaba Halmos's statement on regulation of right to strike soon to come before Parliament Külpolitika: - Algériában egyre súlyosabbá válik a helyzet - Tüntetések voltak Svédországban a romániai falurombolás ellen - Buharin születésének 100. évfordulóját méltatta a Pravda - Lettországon is megalakult a népfront Belpolitika: - "Egy magyar visszanéz" címmel a NYT interjút közölt Kádár Jánossal - Magyarországon 1956 óta 4,5 millió magzatot mészároltak le. Czakó Gábor fejti ki nézeteit a népesedési helyzetről és a gyermekvállalás megtagadásáról - Párttá válik a Demokrata Fórum? - A szervezet egyik alapító tagja, Bíró Zoltán válaszol a kérdésre - Valamennyi svéd párt tiltakozott a romániai falurombolási program ellen - A magyarországi egyházak ökumenikus tanácsa a romániai nemzeti kisebbségek védelme tárgyában írt levele ismertetése - Halmos Csaba a hamarosan parlament elé kerülő sztrájkjog-szabályozásáról nyilatkozott